Effect of time-of-day on biochemical markers in response to physical exercise - Ammar, A.; Chtourou, H.; Souissi, N. (The Journal of Strength and Conditioning Research, 2017)
It is well established that many physiological functions are time-of-day (TOD) dependent, and their circadian rhythms are well documented in healthy populations at resting state. In fact, greater rate of oxidative stress, white blood cell, homocysteine, and muscle damage markers were shown in the early evening (˜18:00 hours), and more efficient antioxidant activity was observed in the early morning (˜06:00 hours). During physical tasks, the majority of the above-mentioned physiological functions increase from pre to post physical exercise with different rates of increases from morning to evening. These different rates of increases are suggested to alter the physiological resting diurnal variation. In this context, given the possible significant interaction "TOD × physical exercise," circadian rhythms of the physiological responses during physical activity are still not well established in trained subjects. Otherwise, it was suggested that the diurnal variation of these biochemical parameters could, in part, explain the typical diurnal fluctuation of physical performance. Therefore, the aim of this review was to summarize the currently available studies investigating the circadian rhythms of physiological functions at rest and after physical exercise and to establish their possible effect on the diurnal variation of sport performance. Although studies in this field are limited, the available information shows that compared with sedentary subjects, trained population maintained similar diurnal variations of hematological parameters, homocysteine, and some biochemical markers at rest and even after physical exercise. However, after strength exercises, the circadian rhythms for the majority of oxidative stress and muscle damage markers were altered because of the higher rate of increased pre-post exercises registered in the morning compared with the afternoon and evening. The available studies reveal that the significant circadian variation observed for sport performances could be more likely explained by the alteration of ionic movement and the diurnal fluctuation of homocysteine, lactate, muscle damage, and antioxidant markers.